1877 Terr. of Dakota Rev. Codes 794, Penal Code, ch. 38, § 456 - (:unkn) unknown (General Publisher, 1877)
Prohibited the carry of any slungshot or weapon of similar kind. Violators guilty of a felony.
--
Keywords: CARRY - NON-GUN ARMS